Diagnosis and Management of Rare Case of Mesenteric Hematoma Rupture after Transcatheter Aortic Valve Replacement (TAVR): A Case Report and Review of the Literature - Danish Abbasi; Jeffrey E. Vanhook; Khashayar Salartash; Howard Levite (Case Reports in Vascular Medicine)
We present a case of a 78-year-old female with history of diastolic heart failure and paroxysmal atrial fibrillation on apixaban presenting with worsening shortness of breath. She underwent transesophageal echocardiogram showing severe aortic stenosis with a valve area of 0.8 cm2. Coronary angiography did not reveal significant coronary artery disease. CT of chest, abdomen, and pelvis did not show any evidence of hematoma or dissection. Patient was scheduled for transfemoral TAVR. Patient’s apixaban was discontinued prior to the procedure. She received heparin during the procedure. She successfully underwent left transfemoral aortic valve replacement. Shortly after the procedure, she complained of abdominal pain and became hypotensive. Blood pressure was 76/44 mm of Hg (MAP 58). Hemoglobin dropped to 8.1 g/dl (baseline 13). Stat CT abdomen and pelvis showed a large volume of hemorrhage in the peritoneal cavity. CTA of abdomen showed no evidence of aortic aneurysm or dissection but active extravasation below the inferior aspect of the spleen. Catheterization of the superior mesenteric artery (SMA) identified ileal branch of SMA as the source of bleeding. Embolization using gel foam slurry followed by a coil insertion was performed. Repeat angiogram demonstrated continued extravasation through arcade collaterals. A rapid exploration of the abdominal cavity revealed ruptured mesenteric hematoma. Evacuation of hematoma was performed. Portion of small ileum and bleeding mesenteric branch vessel was resected. Her condition stabilized with no postoperative bleeding and she was discharged on warfarin postoperatively. Use of antithrombotic therapy increases risk of bleeding in TAVR patients. Mesenteric hematoma rupture if not identified can be life-threatening. We believe that this is the first reported case of mesenteric hematoma rupture after a TAVR procedure.